2004
DOI: 10.1111/j.1600-0420.2004.00330.x
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors for survival after enucleation for choroidal and ciliary body melanomas

Abstract: ABSTRACT.Purpose: To evaluate prognostic factors for the survival of patients treated by enucleation for choroidal and ciliary body melanomas. Methods: The study included 293 consecutive patients (147 men and 146 women) treated by enucleation for a choroidal or ciliary body melanoma during the period 1955-2000. The median age at treatment was 61 years (range 26-88 years). Clinical and histopathological findings, vital status at October 1st, 2002, and cause of death were registered. Prognostic factors for survi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
21
1
8

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 48 publications
5
21
1
8
Order By: Relevance
“…5,6 UMs affect both sexes in equal numbers, but males have been reported to show higher disease-specific mortality. 7,8 Lower survival rates in males have also been reported in cutaneous melanoma. 9 This is believed to correlate with more aggressive histology in males.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 UMs affect both sexes in equal numbers, but males have been reported to show higher disease-specific mortality. 7,8 Lower survival rates in males have also been reported in cutaneous melanoma. 9 This is believed to correlate with more aggressive histology in males.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] Largest tumour diameter is currently the most widely used predictor of metastatic disease. 4,[10][11][12][13][14] This factor also correlates with extraocular spread and hence chances of orbital recurrence. 5,15 After conservative therapy, LTD is associated with increased risk of local tumour recurrence, exudative retinal detachment, neovascular glaucoma, and other ocular complications.…”
mentioning
confidence: 99%
“…2,9,18,22,23 Several studies have shown that the size of the uveal melanoma is a risk factor for subsequent metastases. 22,24,25 In the multivariate analyses, we found that large basal tumour diameter was the only significant predictive factor for metastatic disease. The differences in tumour size could therefore explain the difference between the mortality curves in the two treatment groups.…”
Section: Discussionmentioning
confidence: 81%